E3 Ubiquitin Ligases as Molecular Targets in Human Oral Cancers - Masumoto, Kazuma; Kitagawa, Masatoshi (Current Cancer Drug Targets, 2016)
The ubiquitin-proteasome pathway is involved in various biological processes. Several oncogenic E3 ligases target tumor suppressor proteins for ubiquitin-mediated degradation. Alternatively, some other E3 ligases play as a tumor suppressor specifically targeting oncogene products. Deregulation of these E3 ligases induces unbalance between oncogenic signal and tumor suppressor pathway and leads to cellular transformation, tumor growth and metastasis in various human malignancies including oral, and head and neck cancers. Facilitated degradation of the cyclin-dependent kinase (CDK) inhibitor p27Kip1 has been observed in oral, and head and neck cancers, and is correlated with their poor prognosis. SCFSkp2, KPC complex, Pirh2 and CRL4DDB2-Artemis have been reported as E3 ligases targeting p27Kip1 for degradation. In oral cancers, it is reported that overexpression of Skp2 and Pirh2 is associated with poor prognosis. Thus, chemical inhibitors against these E3 ligases are applicable for oral cancer therapy. Some potential compounds that inhibit E3 ligase activity of SCFSkp2 have been reported. Moreover, the HECT-type E3 ligase WWP family and Smurf1 are also involved in the development and growth of human oral cancers. Therefore, small molecule inhibitors against HECT-type E3 ligases are discussed as anti-oral cancer drugs.
Keywords: Skp2